Some Problems with episteme - Woleński, Jan (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
The presented paper analyses the problem of episteme as knowledge being certain. If episteme is to be such, its truth is absolute. Episteme in the above sense was always associated with rationalism (nativism) and apriorirism. If a philosopher-empiricist rejects episteme, he or she has difficulties with explaining the status of logic and mathematics. On the other hand, the explanation of the possibility of episteme requires the acceptance of very strong epistemological and ontological assumptions. Since the rationalists offer principally different view on the nature of episteme, one can have doubts whether rationalism does not lead to irrationalism.